Importance of bone biopsy in the diagnose on the bone metabolic diseases - Hidalgo, Arquímedes (2021)
Objective. To evaluate the importance of bone biopsy in the diagnose of the bone metabolic diseases, its relationship with bone densitometry (BMD) and biomarkers. Methods. In a descriptive, transversal study, 38 biopsies of pelvic bone were made, 36 in female (34 postmenopausal and 2 premenopausal) and 2 in male. All had BMD in spine, hip and/or forearm measured by dual x-ray absorptiometry. Calcium, phosphorus, parathormone, vitamin D, alkaline phosphatase, osteocalcin, hemoglobin, transaminases, total protein and fractions were measured in blood and N-telopeptide of collagen type I, calcium and phosphorus in urine by conventional methods. Results. The mean age of 34 menopausal women was 58 ± 7,79 and menopause time was 11,48 ± 8,76 years; mean BMD in spine, hip and forearm were -2,88 ± 1,16, -2,13 ± 0,82, y - 5,14 ± 1,76, respectively; bone biopsy demonstrated osteoporosis in 33 y Paget´s disease in one. Male persons 48 and 63 years old had BMD in forearm -3,2 and -4,9, and osteoporosis in biopsy. A woman 34 years old had a BMD of -3 and osteoporosis en bone biopsy, a woman 29 years old with BMD -3 presented osteomalacia in biopsy. There was a negative correlatión between age and time of menopause with BMD decrease. Conclusions. A negative correlation between the age and time of menopause with BMD decrease was found. A low BMD not always is osteoporosis, it might be other bone metabolic disease like osteomalacia or Paget´s disease. Bone biopsy is a more trustworthy procedure for the diagnose of these diseases.